DEVELOPMENT OF ETHNO-STEAM-BASED LIVE WORKSHEETS ON SENDANG LESTARI BATIK TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' SCIENCE LITERACY IN TEMPERATURE AND HEAT TOPICS - Revi Yuanita; Mar’atus Revana; Firda Shofiana; Hasan Subekti (Adisam Publisher, 2026)
This research aims to improve junior high school students' science literacy on temperature and heat through the implementation of Ethno-STEAM-Based Live Worksheets on Sendang Lestari Batik. Live Worksheets is an interactive online platform that transforms conventional activity sheets into engaging digital formats. This study is motivated by the low level of students' science literacy on temperature and heat topics. The development of STEAM-based e-LKPD (electronic student worksheets) is necessary to meet 21st-century learning demands. The Ethno-STEAM approach integrates local wisdom (batik) with science, technology, engineering, arts, and mathematics. The ethnoscience aspect of this study is batik. This research employs the ASSURE model. The validation test results show that the live worksheet meets the